2012
DOI: 10.1016/j.jpsychires.2011.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of performance in adolescents at risk for schizophrenia: Inefficiently increased cortico-striatal responses measured with fMRI

Abstract: Background fMRI studies indicate that schizophrenia patients and their adult relatives require greater prefrontal activation to maintain performance at levels equal to controls, but studies have not established if this pattern of inefficiency is observed in child and adolescent offspring of schizophrenia patients (SCZ-Off). Methods Using a task with visual working memory demands, we investigated activation in cortico-striatal networks and dorsal prefrontal modulation of regions underlying visual working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…Results of this study are provocative, as left PHP, left caudate, and right DLPFC are strongly implicated in studies of CHR, schizophrenia, and familial risk for psychosis (e.g., (Diwadkar et al, 2012; Fusar-Poli et al, 2011d; Kuepper et al, 2013; Seidman et al, 2003; Seidman et al, 2006; Tamminga et al, 2010; Tandon et al, 2013; Thermenos et al, 2013). Converging evidence points to both structural, functional and/or neurochemical abnormalities in these three regions in CHR.…”
Section: Discussionmentioning
confidence: 83%
“…Results of this study are provocative, as left PHP, left caudate, and right DLPFC are strongly implicated in studies of CHR, schizophrenia, and familial risk for psychosis (e.g., (Diwadkar et al, 2012; Fusar-Poli et al, 2011d; Kuepper et al, 2013; Seidman et al, 2003; Seidman et al, 2006; Tamminga et al, 2010; Tandon et al, 2013; Thermenos et al, 2013). Converging evidence points to both structural, functional and/or neurochemical abnormalities in these three regions in CHR.…”
Section: Discussionmentioning
confidence: 83%
“…PET studies have found increased striatal dopamine neurotransmission in schizophrenia patients (Abi-Dargham et al, 1998Kegeles et al, 2010), individuals with prodromal signs of schizophrenia Howes et al, 2009), and their unaffected first-degree relatives (Hirvonen et al, 2005;Huttunen et al, 2008). Taskbased functional neuroimaging studies have also found altered striatal activity in high risk subjects during various tasks, including inhibitory control tasks , anti-saccades , as well as tasks of sustained attention (Diwadkar et al, 2011) and visual working memory (Diwadkar et al, 2012). However, striatal findings in schizophrenia have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using PET, Hirvonen et al report increased caudate D2 receptor availability in unaffected co-twins of patients with schizophrenia (Hirvonen et al, 2005). Furthermore, a recent t-fMRI study of children of patients with schizophrenia suggests inefficient frontostriatal responses during a working memory task (Diwadkar et al, 2012). Alterations in cortico-subcortical functioning may characterize schizophrenia diathesis and reflect vulnerability for the illness.…”
Section: Introductionmentioning
confidence: 99%
“…All statistical analyses were conducted using a cluster-level correction approach that has been formally characterized (Ward, 2000) and utilized in several imaging related studies (Ladouceur et al, In Press; Hagler et al, 2006; Bakshi et al, 2011; Diwadkar et al, 2011a; 2011b; Diwadkar et al, In Press). The approach is based on “n” Monte Carlo simulations of the process of image generation, spatial correlations of voxels (i.e., clusters), voxel intensity thresholding (voxel-level values), probability thresholding, and minimum cluster size thresholding where the probability of a true positive detection of a significant cluster is determined from the simulations themselves.…”
Section: Methodsmentioning
confidence: 99%